A project co-created with the community to mitigate loneliness in midlife women - Corsini, Nadia; Dorman, Fiona; Scott, Jodie; Wright, Amanda; Turnbull, Deborah; Williams, Carmel; Bates, Deborah; Reading, Bernadette; Everuss, Hayley; Peng, Fanke; Pearse, Rachael; Eckert, Marion (Frontiers in Public Health, 2024)
This paper describes how a team of researchers, policy stakeholders and community members came together to co-create prevention-oriented and community-informed solutions to address loneliness in women -The Loneliness Project. We adopt the definition of co-creation offered by Vargas et al. (2022) as a "collaborative approach of creative problem solving between diverse stakeholders at all project stages" (1). Our aim is to encourage community partnerships and collective effort to address public health approaches to loneliness by developing a shared understanding of the issue from multiple perspectives and through the co-creation process, highlighting the key factors for co-creating a funding application for a community demonstration project.